A Schiff base sensor for relay monitoring of In3+ and Fe3+ through "off–on–off" fluorescent signals. (29th March 2021) - Li, Bing; Liu, Zhihua; Li, Linlin; Xing, Yujing; Liu, Yuanying; Yang, Xiaofeng; Pei, Meishan; Zhang, Guangyou
Abstract : A Schiff base N ′-(3-ethoxy-2-hydroxybenzylidene)-4, 5-dihydronaphtho[1, 2- b ]thiophene-2-carbohydrazide (LB2 ) was designed and synthesized and could be used as a sensor to identify In 3+ and Fe 3+ through fluorescence 'off–on–off' behavior. Abstract : A Schiff base N ′-(3-ethoxy-2-hydroxybenzylidene)-4, 5-dihydronaphtho[1, 2- b ]thiophene-2-carbohydrazide (LB2 ) was designed and synthesized based on 4, 5-dihydronaphtho[1, 2- b ]thiophene-2-carbohydrazide and 3-ethoxy-2-hydroxybenzaldehyde, and could be used as a sensor to identify In 3+ and Fe 3+ through fluorescence 'off–on–off' behavior. The probe LB2 showed high sensitivity and selectivity towards In 3+ and Fe 3+ in the presence of other metal ions with detection limits of 8.05 × 10 −9 M and 2.59 × 10 −8 M, respectively. The structure of LB2 was characterized by 1 H NMR, 13 C NMR, FTIR and mass spectrometry. The complexation ratio of LB2 to In 3+ and Fe 3+ was 1 : 1 for both which was verified by mass spectrometry and the Job plot. The binding mode and sensing mechanism of LB2 with In 3+ and Fe 3+ were also verified.